Bolton tooth size analysis in a sample of Sudanese adults - Mustafa, Raja AbdAlgadir; Abuaffan, Amal Hussein (Brazilian Dental Science, 2021)
Introduction: A correct proportion between the upper and lower teeth is critical to achieving proper occlusal interdigitation, ideal overjet, and good molar intercuspation at the end of orthodontic treatment. Objectives: To determine the anterior and overall Bolton’s ratio in the Sudanese population, investigate gender differences in tooth size ratios, and to compare these results with Bolton’s original ratio norm. Material and Methods: The sample consisted of dental casts of 104 Sudanese University students with normal occlusion (52 females, 52 males), aged between 16-26 years randomly selected from AL- Neelain University. An electronic digital caliper was used to measure the mesiodistal tooth size of the maxillary and mandibular teeth anterior to the second molars. These measurements were then used to obtain Bolton’s ratio. Mean, range, and standard deviation of the anterior and overall ratios were computed for each subject. T-Tests were used to compare gender differences and to investigate differences between the results of this study and Bolton’s original ratio. Results: Anterior and overall Bolton ratios for males were 78.43±2.44 and 93.901±9.8 and for females were 78.29±2.6 and 91.67±3.3 percent, respectively. There were no statistically significant differences between males and females for the anterior and overall ratios P>0.05. The anterior and overall Bolton’s ratios among Sudanese University students were 78.37 ± 2.54, and 92.79± 7.43 percent, respectively. statistically significant difference between this study and Bolton’s study were found in both anterior and overall ratio P<0.05. Conclusion: Bolton’s mean ratios may not be applicable to Sudanese. Keywords Bolton’s ratio; Sudanese population; tooth-size.